THE EFFECTS OF ALTI-VIT ON EXERCISE PERFORMANCE AT ALTITUDE. Issue 17 (24th October 2013) - Youngman, E; Howe, C; Moir, HJ
Abstract : This study examined the effects of ALTI-VIT supplementation on exercise performance and Acute Mountain Sickness (AMS) at altitude. Seven healthy males with no experience of exercise at altitude completed two 16 km cycle time-trials at a simulated altitude of 2400 m in an altitude chamber. Using a single-blind, randomised, crossover design, participants consumed 2 capsules (270 mg) of ALTI-VIT (A) or a placebo (Pl) 24-hours prior to testing and 2 capsules on the morning of testing. Time-trial completion was faster in the A condition (30.04±4.39 min) than the Pl condition (31.02±5.22 min) ( P =0.05). RER was lower in the A condition (A: 1.03±0.11 vs . Pl: 1.13±0.12; P =0.044) and the incidence of AMS (A: 0.4±0.5 vs. Pl: 3±1; P =0.002) and severity of symptoms were reduced ( P <0.05). No differences were found between conditions for HR, RPE, VO2, VE, VO2 max, speed, power output and RPM ( P >0.05). These results demonstrated that 24-hour supplementation of ALTI-VIT enhanced exercise performance at altitude and reduced the incidence and severity of AMS.